PERAN EKONOMI KREATIF TERHADAP PENGEMBANGAN JIWA ENTREPRENEURSHIP DI LINGKUNGAN PESANTREN: STUDI KASUS DI PONDOK MODERN DARUSSALAM GONTOR PUTRI 1 - Ririn Noviyanti (LP3M IAI Al-Qolam, 2017)
Today, by effectuation of the Asian Economic Community (AEC), the competition will be increas-ing the quality of human resources. It presents a consequence for every individual to constantly develop and improve their quality. No exception to human resources who live in boarding schools. Boarding School community needs to improve its quality to be competitive arena of the world of work. Therefore, coaching that done in a boarding schools, should reflect and provide education about the importance of self-reliance, especially in the financial sector. This study aims to analyze the role of the creative economy to the development of entrepreneurial spirit in a boarding schools education system that has applied entrepreneurship education as a means to train financial independence of the students By using the phenomenological approach, this qualitative research began with the collection of data through observation and documentation for later analysis so found some creative economic role towards developing the spirit of entrepreneurship in boarding schools. The conclusion from this study is that the creative economy has some important role in the deve-lopment of the spirit of entrepreneurship in boarding schools. There are: (1). Stimulate creative and innovative behavior on a product / service. (2). Explore and hone skills (3). Providing knowledge with methods of learning by doing (4). Provide training on the analysis of SWOT (Strength, Weak-ness, Opportunity and Threat). This study is limited to the analysis of the role of the creative economy to the development of entre-preneurship spirit in boarding schools, especially in Pondok Pesantren Darussalam Gontor Putri 1 so that it can’t be generalized to the other boarding schools.